2022
DOI: 10.1108/ejm-07-2021-0505
|View full text |Cite
|
Sign up to set email alerts
|

The interaction of social influence and message framing on children’s food choice

Abstract: Purpose Obesity leads to increased mortality and morbidity among children, as well as when they turn adults. Melding marketing theories in social influence and message framing, this study aims to examine how compliance versus conformance social influence, each framed either prescriptively or proscriptively, may guide children’s choice of healthy versus unhealthy food. Design/methodology/approach This study conducted two experiments in a Pakistani junior school. Experiment 1 exposed children to either a presc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 79 publications
0
3
0
Order By: Relevance
“…However, there is limited evidence that these information-based policies contribute to reducing levels of obesity in the population (Cowburn and Stockley, 2005; Grunert and Wills, 2007; Vecchio and Cavallo, 2019). This could be because of a variety of personal, social and environmental factors (Block et al , 2011; Khan et al , 2022; Lau et al , 2022; Mazzocchi et al , 2009), but an increasing body of evidence shows that consumers struggle to process the available information because of numeracy constraints and other cognitive limitations (Cowburn and Stockley, 2005; Hagmann and Siegrist, 2020; Just and Payne, 2009; Vecchio and Cavallo, 2019; Yan et al , 2016).…”
Section: Introductionmentioning
confidence: 99%
“…However, there is limited evidence that these information-based policies contribute to reducing levels of obesity in the population (Cowburn and Stockley, 2005; Grunert and Wills, 2007; Vecchio and Cavallo, 2019). This could be because of a variety of personal, social and environmental factors (Block et al , 2011; Khan et al , 2022; Lau et al , 2022; Mazzocchi et al , 2009), but an increasing body of evidence shows that consumers struggle to process the available information because of numeracy constraints and other cognitive limitations (Cowburn and Stockley, 2005; Hagmann and Siegrist, 2020; Just and Payne, 2009; Vecchio and Cavallo, 2019; Yan et al , 2016).…”
Section: Introductionmentioning
confidence: 99%
“…In contrast, another study of message-framing effects on eating choices in children found the gain frame to yield positive effects but not the loss-frame message (Binder et al, 2020). Still, other studies have found that both gain- and loss-framed messaging can be effective to promote healthy eating in children, but results may depend on the nature of the behavior targeted by the message (Khan et al, 2022; Wyllie et al, 2015). In sum, there is limited research on message framing with children.…”
Section: Factors That Influence Children’s Risk Takingmentioning
confidence: 99%
“…The results also show that the main effect is moderated by individual factors such as whether or not the person has a health condition and shopping situations that involve time pressure. Continuing, Khan et al (2022) examine how compliance versus conformance social influence, each framed either prescriptively or proscriptively, may guide children's choice of healthy versus unhealthy food. Based on two experiments in Pakistan, the results show that proscriptive is stronger than prescriptive compliance influence in nudging children to pick fruits (healthy) over candies (unhealthy).…”
Section: Articles In the Special Issuementioning
confidence: 99%